2013
DOI: 10.1371/journal.pone.0076379
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Secretion of CCL22 Activates Intratumoral Treg Infiltration and Is Independent Prognostic Predictor of Breast Cancer

Abstract: It has been reported that dense intratumoral infiltration of Foxp3 +Tregs (Tregs) was an independent factor for poor prognosis of breast cancer (BC) patients. However, the cytokines activating the Treg infiltration are not known. This study was undertaken to evaluate the role of CCL22 and TGF-β1 in this cascade and their prognostic significance for BC patients. 417 cases of invasive breast cancer were selected from the prior study cohort and the expressions of CCL22 and TGF-β1 were assessed by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 36 publications
3
54
0
6
Order By: Relevance
“…It has been proved that Tregs can be recruited to tumor microenvironment by CCL22 in ovary (22), prostate (23), gastric (9), esophageal (24), hepatocellular (25), and breast carcinomas (26)(27)(28). Qin and colleagues (10) found that CCL22 can recruit Tregs into MPE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that Tregs can be recruited to tumor microenvironment by CCL22 in ovary (22), prostate (23), gastric (9), esophageal (24), hepatocellular (25), and breast carcinomas (26)(27)(28). Qin and colleagues (10) found that CCL22 can recruit Tregs into MPE.…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box protein 3 (Foxp3) is a key regulator for the development and function of Treg [16,17], and serves as the most specific marker to label the CD4+CD25+ Treg in human cancers [14,18]. Treg can be locally induced or selectively recruited into the tumor microenvironment mediated by IL-10, TGF-b or CCL22 [19][20][21]. The accumulation of Tregs can subsequently inhibit the host antitumor immune response, via cell-cell contact or secreting immunosuppressive cytokines, such as IL-10, IL-35 or TGF-b [15,19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, CCL22 has important effect on suppressing immune responses to microbial infections and tumor cells by its ability to recruit Th2-and Treg cells, thereby enhancing microbial persistence and tumor development [17]. The higher expression of CCL22 has been implicated in some cancers, including colorectal adenocarcinomas [18], lung cancer [19] breast cancer [20], lymphoma [21], and head and neck squamous cell carcinoma [22].…”
Section: Introductionmentioning
confidence: 99%